PERAN KONSELOR DALAM MEMBENTUK KARAKTER PESERTA DIDIK di ERA GLOBALISASI - Pardi, Pardi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
The role of counselors has become increasingly complex with the advancement of technology and social changes in the modern era. Researchers examine the challenges and opportunities faced by counselors in providing academic, career, and socio-emotional guidance for students. Based on a literature review, it is found that counselors need to develop adaptive skills. Counselors should understand the evolving digital technology, safeguard client data, and uphold higher ethical standards in their practice. Additionally, counselors must continuously update their knowledge through ongoing education and research to enhance the quality of counseling services. This is crucial for preparing a young generation that is mature in independence, emotional management, and decision-making.